Synthesis, Spectroscopic Properties, Thermal Properties and Aggregation Behaviors of Macrogol-Substituted Phthalocyanines - Şahin, S.; Aģar, E. (Elsevier B.V., 2019)
The synthesis, characterization, spectroscopic data, solubility and aggregation behaviors depend on the solvents of metalled (Co, Cu, Ni, Zn) and metal free pegylated phthalocyanines (Pcs) were reported. Precursor phthalonitrile compound (4) for phthalocyanine formation was synthesized by nucleophilic substitution reaction between tetraethylene glycol substituted phthalonitrile (2) and tetraethylene glycol monotosylate (3). Related phthalocyanines (4-H, 4-Co, 4-Cu, 4-Ni, and 4-Zn) were characterized by FT-IR, 1 H NMR, 13 C NMR, and UV–Vis spectroscopies and elemental analysis. Thermal stabilities of the phthalocyanines were determined in the range between room temperature and 1000 °C. Pegylated phthalocyanines showed high solubility in water and common organic solvents including methanol, ethanol, acetone, pyridine, 1,4-dioxane, dimethylformamide, dimethylsulfoxide, dichloromethane, and chloroform. Aggregation states of all phthalocyanines were investigated in the aforementioned solvents using UV–Vis spectroscopy method. All phthalocyanines were especially found highly aggregated in their aqueous solutions. © 2019 Elsevier B.V.
Keywords: Macrogol; Pegylation; Phthalocyanine; Phthalocyanine Aggregation; Polyethylene Glycol; Water Solubility